Indonesia of Batik Trusmi MSMEs: The Effect of User Technology Capability on Individual Performance with the Accounting Information Systems Effectiveness - Tita Borshalina, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to obtain empirical evidence of the effect of user technology capability on individual performance in Indonesian Batik Micro, Small, and Medium Enterprises (MSMEs); and to obtain empirical evidence the accounting information systems effectiveness moderates the effect of user technology capability on individual performance in Batik MSMEs. This study used an associative quantitative method that states the relationship of two or more variables. The data source used in this study is the primary data source in the form of a questionnaire filled by employees of Batik Trusmi MSMEs as unit analysis. The data analysis technique used in this study uses the analysis of Moderated Regression Analysis (MRA). The study result indicated that user technology capability has a positive on individual performance in Batik Trusmi MSMEs and the accounting information systems effectiveness proven to moderate the effect of user technology capability on individual performance in Batik Trusmi MSMEs. Therefore, the technical ability of individuals as users of information systems plays an important role in the development of information systems in order to produce the best information for making accurate planning reports so it will improve of MSMEs for the better performance.